APPLICATION OF FLEXIBILITY MODELS BY INSTITUTIONS OF HIGHER EDUCATION IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Verbovska, L. S. (The actual problems of regional economy development, 2023)
The purpose of the scientific article is to study the application of flexibility models in the management of higher education institutions in accordance with the goals of Sustainable Development. The article substantiates the necessity of applying flexibility models in the management of a higher education institution. The article examines the main "Sustainable Development Goals: Ukraine", presents a vision of the guidelines for Ukraine's achievement of the Sustainable Development Goals (SDGs), which were approved at the UN Sustainable Development Summit in 2015. Based on the results of the analysis of the main goals, the need to ensure sustainable competitive advantages of higher education institutions through academic mobility programs: programs of double diplomas, academic exchanges of students and teachers is substantiated; formation of areas of cooperation, prioritization of international research; active participation of scientific and pedagogical staff in international projects; foreign career guidance, holding international scientific-technical and management conferences and/or research at the appropriate level; teaching disciplines, lecture courses in foreign languages; to harmonize relations between business entities, the scientific community, higher education institutions and other interested parties; flexibility in management, resources, external environment, development of competences of scientific and pedagogical workers; the ability to cooperate with students of higher education in building their educational trajectory within the framework of a student-centered learning model. It is substantiated that issues of sustainable development are integrated into the system of professional education at all levels of education by ensuring the integration of issues of sustainable development into various forms of education. It has been proven that modern higher education institutions faced external challenges for which they were essentially unprepared. The directions for the implementation of flexibility models have been formed, which should be designed based on the Sustainable Development Goals, strategic and operational tasks, opportunities and potential; management style; organizational culture; external and internal functioning of the institution of higher education.